PENGEMBANGAN MEDIA FLASHCARD BERBASIS KEARIFAN LOKAL SUKU SASAK PADA MATERI BAHASA INDONESIA SISWA KELAS II SDN 11 PRAYA - Erni Yulida; Muhammad Tahir; Vivi Rachmatul Hidayati; Mansur Hakim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the feasibility of flashcard media based on local wisdom of the Sasak tribe, namely songket, as a learning media for Indonesian language for class II. The type of research used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were teachers and students of class II of SDN 11 Praya, while the object was flashcard media based on local wisdom of the Sasak tribe. The instruments used included observation sheets, interviews, expert validation, and teacher and student response questionnaires. The validation results showed that flashcards were declared "Very Valid" by media experts with a percentage of 93%, material experts with a percentage of 88.5%, and language experts with a percentage of 91.4%. Small and large group trials obtained the category "Very Practical" with percentages of 93.85% and 96.35% respectively. Based on these results, flashcards based on local wisdom of the Sasak tribe were declared very feasible to use in learning.